Trend of Sex Related Crimes in Varanasi District - Shashank Shekhar Jha; Manoj Kumar Pathak (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Sexual harassment and sexual assault both rely on dehumanizing the intended victims. Sexualviolence is a significant cause of physical and psychological harm and suffering for women and children.The Indian Penal Code (IPC) is the crucial criminal code of India.Material and Method: Consent of the victim and accused was taken prior to examination. In case of minor,the consent from his/her parents or legal guardian was taken. SAFE (Sexual Assault Forensic Evidence) kitwas used for sample collection from sexual assault victims and accused.Observation and Result: This study includes cases 160 victims of sexual assault.Conclusion: The present study, being a pioneer one, is relevant in the context of crime against women ofall age groups in the Eastern U.P., especially of Varanasi district in socio-demographic and medico-legalparadigms. The government must set up a special unit that recruits officers specifically to deal with sexualoffences, and create easy access to doctors, forensic experts, rape survivors and psychologists.